2006
DOI: 10.1080/01443610500378590
|View full text |Cite
|
Sign up to set email alerts
|

Gi protein-mediated translocation of serine/threonine phosphatase to the plasma membrane and apoptosis of ovarian cancer cell in response to gonadotropin-releasing hormone antagonist cetrorelix

Abstract: Serine/threonine protein phosphatase 2A (PP2A), a crucial enzyme in apoptosis control, has been demonstrated within the plasma membrane as well as in the soluble fraction. This study aimed to examine hormonal translocation of PP2A to the plasma membrane in gonadotropin-releasing hormone (GnRH)-responsive ovarian cancer cells. Apoptosis of ovarian cancer cell lines Caov-3 and SK-Ov-3 was quantified by nuclear morphology after staining with Hoechst 33342 dye. PP2A protein and activity in plasma membrane were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…The GnRH-II antagonist-induced increase of caspase-3 activity was reduced by pertussis toxin, indicating that it is mediated at least in part by G protein ai. Comparable data were obtained by Imai et al (26). They have shown that GnRH-I antagonist cetrorelix-induced apoptotic cell death of human ovarian cancer cells was mediated through pertussis toxin-sensitive Gi protein-linked GnRH receptor.…”
Section: Discussionsupporting
confidence: 68%
“…The GnRH-II antagonist-induced increase of caspase-3 activity was reduced by pertussis toxin, indicating that it is mediated at least in part by G protein ai. Comparable data were obtained by Imai et al (26). They have shown that GnRH-I antagonist cetrorelix-induced apoptotic cell death of human ovarian cancer cells was mediated through pertussis toxin-sensitive Gi protein-linked GnRH receptor.…”
Section: Discussionsupporting
confidence: 68%
“…Expression of CIP2A, studied in 562 serous ovarian cancer patients by IHC, showed strong cytoplasmic staining in 40% of the samples and was associated with high grade, advanced stage and poor outcome (195).On the other hand, inhibition of PP2A was essential for the apoptosis induced by doxorubicin (196) and translocation of PP2A to plasma membrane was essential for gonadotropin-releasing hormone (GnRH) antagonist, cetrorelix induced apoptosis in GnRH responsive ovarian cancer cells (197).…”
Section: Inactivation Of Pten By Genetic Mutation Is Well-known In Omentioning
confidence: 99%
“…An equimolar concentration of the GnRH‐I antagonist cetrorelix induced apoptosis by upregulating p53 and p21 protein levels, whereas concentrations as low as 10 −9 m resulted in antiproliferative effects [46]. Recently, apoptosis was shown to be induced by a low concentration of cetrorelix in ovarian cancers [50]. We also observed DNA fragmentation after prolonged (6 days) low‐dose GnRH‐I agonist treatment [36].…”
Section: Antiproliferative Effect Of Gnrh Analogs On Ovarian Cancermentioning
confidence: 86%